Development and Validation of a Prognostic N6-Methyladenosine-Related Immune Gene Signature for Lung Adenocarcinoma - Zhang L (Dove Medical Press, 2021)
Lemeng Zhang, Yongzhong Luo, Tianli Cheng, Jianhua Chen, Hua Yang, Xiaoping Wen, Zhou Jiang, Haitao Li, Changqie Pan Thoracic Medicine Department 1, Hunan Cancer Hospital, Changsha, Hunan Province, 410013, People’s Republic of ChinaCorrespondence: Yongzhong Luo Tel/Fax +86-731-89762220Email luoyongzhong@hnca.org.cnPurpose: The prognostic value of an N6-methyladenosine (m6A) methylation-related immune gene signature for lung adenocarcinoma (LUAD) was investigated.Patients and Methods: Gene expression and clinical phenotype data of LUAD patients were downloaded from The Cancer Genome Atlas database. A list of immune-related genes was retrieved from the InnateDB database. Correlation analysis, survival analysis, and univariate and multivariate Cox regression analyses were performed. After allocating patients into a high-risk or a low-risk group, the corresponding survival rates, immune microenvironment, expression of immune checkpoint genes, and modulation of Kyoto Encyclopedia of Genes and Genomes pathways were examined. Finally, the expression levels of prognostic biomarkers were assessed in the GSE126044 dataset.Results: Seven m6A-related immune prognostic genes were identified. High expression of PSMD10P1, DIDO1, ABCA5, and CIITA was associated with high survival rates, while that of PRC1, ZWILCH, and ANLN was associated with low survival rates. The high- and low-risk groups showed significant differences in terms of the abundance of six tumor-infiltrating immune cell types and expression of 12 immune checkpoint genes. The risk group acted as an independent prognostic factor (hazard ratio = 0.398, 95% confidence interval = 0.217– 0.729, P = 0.003). Finally, the developed nomogram could predict most efficiently the 1-, 2-, and 3-year survival probability of LUAD patients with a C-index of 0.833.Conclusion: A seven-gene risk signature, associated with the immune microenvironment in LUAD, showed independent prognostic value.Keywords: lung adenocarcinoma, N6-methyladenosine methylation, immune-related genes, immune microenvironment, prognostic signature